Revitalizing geometry education: The role of indigenous pedagogies in Kalomo district’s secondary schools - Mulenga, Eddie Mumba; Folokwe, Kingster; Spangenberg, Erica Dorethea (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Mainstream education often marginalizes the cultural heritage and indigenous knowledge systems of local communities, particularly in mathematics instruction. This study investigates the integration of indigenous pedagogies into geometry education to enhance student engagement and cultural responsiveness. Grounded in a critical constructivist paradigm, the study recognizes knowledge as co-constructed through learners’ cultural experiences and emphasizes the transformative potential of indigenous worldviews in shaping mathematical understanding. It employs a qualitative case study design to explore how traditional knowledge impacts student performance and the challenges faced in its incorporation. Data were collected from teachers, administrators, community elders, and students through interviews, focus groups, and classroom observations. Findings through thematic analysis revealed that indigenous pedagogies, such as traditional geometric patterns and community involvement, enhance student engagement, cultural pride, and geometry performance. Moreover, students demonstrated improved conceptual understanding and enthusiasm when learning activities reflected their cultural contexts. However, challenges include resource limitations, curriculum rigidity, and insufficient professional development. The study recommends creating resources tailored to indigenous pedagogies, greater curricular flexibility, and enhanced administrative support. It concludes by emphasizing the long-term value of integrating indigenous knowledge in mathematics education, not only to improve learning outcomes but also to contribute to cultural sustainability and educational equity in Zambia.